1999
DOI: 10.1038/sj.bmt.1701759
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting decrease of marrow and circulating long-term culture initiating cells after allogeneic bone marrow transplant

Abstract: Summary:We investigated bone marrow (BM) and circulating (PB) hematopoietic progenitor cells in 37 normal donors and in 25 patients 1 to 8 years after successful allogeneic bone marrow transplant. At the time of testing, transplanted patients had normal blood counts and bone marrow cellularity. By flow cytometry, BM CD34 + cells were found to be three-to four-fold decreased in transplanted patients compared to normal donors, while the number of PB CD34+ cells was the same as in normal donors. Using a methylcel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…The accentuated decline in the CD90 ϩ subset reported here suggests that this deficit is most pronounced in primitive progenitors, and it anticipates the finding that post-BMT reductions in long-term-culture-initiating cells are more profound, and prolonged, than reductions in LCPs. 4,5 Our results imply that early hematopoietic reconstitution after BMT is associated with a compensatory increase in mitotic rate in a population of CD34 ϩ CD90 ϩ progenitors. The accelerated proliferation of these cells is the most likely cause of the striking telomere shortening observed in leukocytes of BMT recipients, 6-8 though direct correlation must be sought in future studies.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The accentuated decline in the CD90 ϩ subset reported here suggests that this deficit is most pronounced in primitive progenitors, and it anticipates the finding that post-BMT reductions in long-term-culture-initiating cells are more profound, and prolonged, than reductions in LCPs. 4,5 Our results imply that early hematopoietic reconstitution after BMT is associated with a compensatory increase in mitotic rate in a population of CD34 ϩ CD90 ϩ progenitors. The accelerated proliferation of these cells is the most likely cause of the striking telomere shortening observed in leukocytes of BMT recipients, 6-8 though direct correlation must be sought in future studies.…”
Section: Resultsmentioning
confidence: 71%
“…The weight of existing evidence suggests that absolute numbers of both subsets are diminished for prolonged periods after transplantation. [1][2][3][4][5] Selleri et al 5 examined the bone marrow of BMT donors and recipients and found 3-to 4-fold fewer CD34 ϩ cells in the marrow of recipients as late as 8 years after BMT. The accentuated decline in the CD90 ϩ subset reported here suggests that this deficit is most pronounced in primitive progenitors, and it anticipates the finding that post-BMT reductions in long-term-culture-initiating cells are more profound, and prolonged, than reductions in LCPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,29 Both observations, the loss of earlier and the gain of more committed CD34 subtypes are in line with other reports. Selleri et al 37 found an eightfold decrease of long-term culture initiating cells in the BM of patients as compared with donors, and Thornley et al 30 described a higher telomere loss in the BM of patients with full donor chimerism. Woolthuis et al 38 reported a loss of quiescence and impaired function of CD34 + /CD38 low cells 1 year after autologous stem cell reinfusion.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for a "dead-band" in the control of HSC numbers, [90][91][92][93] as described in Radivoyevitch et al 87 ; here "dead" refers to the putative nonresponsive character of the HSC feedback control system when HSC numbers are more than sufficient to maintain a hematopoietic system. This postulate is an example of the systems biology concept of bounded autonomy.…”
mentioning
confidence: 99%